2013
DOI: 10.1111/rurd.12012
|View full text |Cite
|
Sign up to set email alerts
|

A Century of the Evolution of the Urban System in Brazil

Abstract: In this paper, we study the hitherto unexplored evolution of the size distribution of 185 urban areas in Brazil between 1907 and 2008. We find that the power law parameter of the size distribution of the 100 largest urban areas increases from 0.63 in 1907 to 0.89 in 2008, which confirms an agglomeration process in which the size distribution has become more unequal. A panel fixed effects model pooling the same range of urban size distributions provides a power law parameter equal to 0.53, smaller than those fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Many authors have used this rank-size procedure; for example, Berry and Garrison (1958) show the cases of spatial hierarchy in Korea and Washington. In more recent years Pumain and Moriconi-Ebrard (1997) show the relevance of Zipf's law for a set of countries with data from 'Geopolis'; (2) Brakman et al (1999) and Mulder and de Groot (2008) study the case of the Nederlands; Benguigui and Blumenfeld-Lieberthal (2010) present findings from Israel; Rozenfeld et al (2011) test the Zipf relevance for American statistical metropolitan areas using a city clustering algorithm; and Matlaba et al (2011) study the size distribution of urban areas in Brazil.…”
Section: The Rank-size Rule For City-size Distributionmentioning
confidence: 99%
“…Many authors have used this rank-size procedure; for example, Berry and Garrison (1958) show the cases of spatial hierarchy in Korea and Washington. In more recent years Pumain and Moriconi-Ebrard (1997) show the relevance of Zipf's law for a set of countries with data from 'Geopolis'; (2) Brakman et al (1999) and Mulder and de Groot (2008) study the case of the Nederlands; Benguigui and Blumenfeld-Lieberthal (2010) present findings from Israel; Rozenfeld et al (2011) test the Zipf relevance for American statistical metropolitan areas using a city clustering algorithm; and Matlaba et al (2011) study the size distribution of urban areas in Brazil.…”
Section: The Rank-size Rule For City-size Distributionmentioning
confidence: 99%
“…Ioannides and Skouras [31], among others, have argued that Pareto-Zipf's law seems to stand in force only in the tail of the data distribution. Matlaba et al [32] also provided such an "evidence that, at least for the analyzed case of Brazilian urban areas over a spectacularly wide period ), Zipf's law is clearly rejected. Soo [33] has also empirically shown that the size of Malaysian cities cannot be plotted according to such a rank-size rule, but a suitable collection of them can do it.…”
Section: Introductionmentioning
confidence: 92%
“…2 For details, see Gabaix and Ioannides (2004). Some examples of empirical works considering Brazil and/or the United States are Ruiz (2005), Matlaba et al (2013) and Chauvin et al (2017).…”
Section: Introductionmentioning
confidence: 99%